Eye Symptom Questionnaire to Evaluate Anterior Eye Health. Issue 6 (November 2018) - Woodward, Maria A.; Valikodath, Nita G.; Newman-Casey, Paula Anne; Niziol, Leslie M.; Musch, David C.; Lee, Paul P.
Abstract : Objectives: Ophthalmologists assess eye complaints with a careful history and eye examination; however, other types of physicians have limited tools to evaluate anterior segment (AS) eye diseases. We identified the eye symptom questions that providers should ask to help determine the presence and urgency of AS eye diseases. Methods: Persons with and without AS disease completed a self-report eye symptom questionnaire (ESQ) based on the National Institutes of Health Toolbox symptom items in an academic center's corneal and comprehensive eye clinics. Gold standard ophthalmic examination determined the presence and urgency of AS disease. The association between reported symptom severity and the probability of AS disease, or urgent AS disease, was evaluated using logistic regression models, and sensitivity and specificity of the ESQ were also calculated. Results: A total of 324 eyes of 162 subjects were included in the study. Of these, AS disease was present in 255 eyes (79%); of which, 111 eyes showed urgent disease. Increasing symptom severity for eye pain (odds ratio [OR]=2.58; P <0.001), glare (OR=2.61; P =0.001), and blurry vision (OR=1.98; P <0.001) were associated with increased odds of AS disease. Increasing symptom severity for eye pain (OR=2.02; P <0.001), eye redness (OR=1.69; P =0.02), and blurry vision (OR=1.41, P =0.01) were associated with increased odds of urgent AS disease. For the primary analysis with mild symptoms considered relevant, the sensitivity of the ESQ to detect AS disease was 83% and to detect urgent AS disease was 92%. Conclusion: Symptoms of eye pain, glare, redness, and blurry vision indicate the presence and urgency of AS disease. Abstract : Supplemental Digital Content is Available in the Text.